2012
DOI: 10.1038/srep00898
|View full text |Cite
|
Sign up to set email alerts
|

Environmental toxins trigger PD-like progression via increased alpha-synuclein release from enteric neurons in mice

Abstract: Pathological studies on Parkinson's disease (PD) patients suggest that PD pathology progresses from the enteric nervous system (ENS) and the olfactory bulb into the central nervous system. We have previously shown that environmental toxins acting locally on the ENS mimic this PD-like pathology progression pattern in mice. Here, we show for the first time that the resection of the autonomic nerves stops this progression. Moreover, our results show that an environmental toxin (i.e. rotenone) promotes the release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
288
2
14

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 355 publications
(319 citation statements)
references
References 46 publications
15
288
2
14
Order By: Relevance
“…exposure to the environmental toxin rotenone (22) as well as following direct injection of adenoassociated viral vectors overexpressing human α-synuclein into the vagus nerve (23). A route from intrinsic enteric neurons to the vagus nerve is supported by the observation that both myenteric neurons and preganglionic vagal nerves express α-synuclein (24).…”
Section: Introductionmentioning
confidence: 72%
“…exposure to the environmental toxin rotenone (22) as well as following direct injection of adenoassociated viral vectors overexpressing human α-synuclein into the vagus nerve (23). A route from intrinsic enteric neurons to the vagus nerve is supported by the observation that both myenteric neurons and preganglionic vagal nerves express α-synuclein (24).…”
Section: Introductionmentioning
confidence: 72%
“…Pan-Montojo et al tested this hypothesis in an eloquent series of experiments that demonstrated the ability of small amounts of rotenone delivered to the enteric nerves to initiate α-syn pathology in mice. Strikingly, resection of the autonomic nerves prevented its spread to the CNS [20].…”
mentioning
confidence: 99%
“…DJ-1 is reported to exert its neuroprotective function in mitochondria (Junn et al, 2009). Many genes involved in Parkinson's disease, among them DJ-1, have been linked to alterations in mitochondrial structure and function and an enhanced sensitivity to mitochondrial toxins like Complex-I inhibitors (Clark et al, 2006;Park et al, 2006;Irrcher et al, 2010;Kamp et al, 2010;Sai et al, 2012;Wang et al, 2012;Burchell et al, 2013). Thus we decided to test the structure and function of mitochondria in the absence of DJ-1 (ΔΔdjr) or complete glyoxalase activity (Δglo), as revealed by staining with MitoTracker CMXRos (Figure 2A) (Pendergrass et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…http://dx.doi.org/10.1101/006916 doi: bioRxiv preprint first posted online Jul. 4, 2014; mitochondria are strongly linked to the appearance of Parkinson's disease (Song et al, 2004;Freire and Koifman, 2012) and impairment of the mitochondrial function is a common feature of both idiopathic and genetic Parkinson's disease (Schapira et al, 1989;Clark et al, 2006;Park et al, 2006;Irrcher et al, 2010;Kamp et al, 2010;Pan-Montojo et al, 2012;Wang et al, 2012;Braidy et al, 2013;Burchell et al, 2013). Our discovery that the production of molecules from endogenous enzymatic pathways can protect neurons, offers a potential therapeutic direction that could include preventive strategies.…”
Section: Discussionmentioning
confidence: 99%